A facile hydrothermal approach for catalytic and optical behavior of tin oxide- graphene (SnO2/G) nanocomposite - Mishra, Yogendra Kumar; Sagadevan, Suresh; Chowdhury, Zaira Zaman; Johan, Mohd Rafie; Khan, Ali Akbar; Aziz, Fauziah Abdul; Rafique, Rahman Faizur; Hoque, Md Enamul (Public Library of Science, 2018)
A cost-effective, facile hydrothermal approach was made for the synthesis of SnO2/graphene (Gr) nano-composites. XRD diffraction spectra clearly confirmed the presence of tetragonal crystal system of SnO2 which was maintaining its structure in both pure and composite materials' matrix. The stretching and bending vibrations of the functional groups were analyzed using FTIR analysis. FESEM images illustrated the surface morphology and the texture of the synthesized sample. HRTEM images confirmed the deposition of SnO2 nanoparticles over the surface of graphene nano-sheets. Raman Spectroscopic analysis was carried out to confirm the in-plane blending of SnO2 and graphene inside the composite matrix. The photocatalytic performance of the synthesized sample under UV irradiation using methylene blue dye was observed. Incorporation of grapheme into the SnO2 sample had increased the photocatalytic activity compared with the pure SnO2 sample. The electrochemical property of the synthesized sample was evaluated.